Morphological responses of forage sorghums to salinity and irrigation frequency - Saberi, Alireza; Hassan, Siti Aishah; Abd Halim, Mohd Ridzwan; Abdul Rahman, Zaharah (Academic Journals, 2011)
Water stress occurs when the demand for water exceeds the available amount during a certain period or when poor quality water restricts its use. In particular, water stress is associated with low availability of water, as well as osmotic effects associated with salinity. The response of forage sorghum [Sorghum bicolor (L.) Moench] varieties to salinity and irrigation frequency were studied from December 2007 to December 2009. Two forage sorghum varieties (Speedfeed and KFS4) were grown under salinity levels of 0, 5, 10 and 15 dS m-1 and irrigated when the leaf water potential reached -1.0 (control), -1.5 and -2.0 MPa. Irrigation frequency and salinity were found to affect the morphology and growth of the forage sorghum. Maximum number of leaves was produced in non-saline soil (13.5 leaves plant-1) with normal irrigation (12.4 leaves plant-1). Low soil water and high salinity reduced the number of leaves as well as the number of tillers produced. Leaf area of plants were also reduced in response to salinity and decreasing soil water availability, while the suppressive effect was magnified under the combined effect of the two factors. Significant differences in stem diameter were found between the frequently and the least frequently watered plants, and stem diameter decreased with increasing salinity. Leaf firing increased with increasing salinity reaching 59.9% in the extreme salinity treatment of 15 dS m-1, and it increased with increasing water stress reaching 48.6% in the extreme water stress treatment of -2 MPa. Under stress condition, the KFS4 variety had a better performance in terms of morphological and growth parameters compared to Speedfeed variety. The threshold concentration was found to vary with variety. However, in control treatment, Speedfeed variety had greater leaf area, plant heights, number of leaf and number of tiller.